1991
DOI: 10.1007/bf00404018
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of biochemical and biomechanical properties of rat tail tendons caused by non-enzymatic glycation and their inhibition by dibasic amino acids arginine and lysine

Abstract: The influence of dibasic amino acids arginine and lysine on non-enzymatic glycation of tail tendon fibers from old (900-day-old) and young (61-day-old) rats was investigated in vitro. The biomechanical changes in tendon fibers of young rats after an incubation interval of 7 or 14 days in a glucose solution were abolished by the addition of arginine or lysine (molar ratio amino acid:glucose 1:10). Glucose incorporation into rat tail tendon fibers as well as Amadori product formation was decreased significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…However, this study did not evaluate changes in short-term diabetic patients. If we consider several reports that have shown that soft tissues exposed to a hyperglycaemic environment are stiffer [10], both our study and that of Salsich et al had unexpected findings. The latter [3], in an effort to find a solution to the contradiction between their study and reports of increased connective tissue stiffness in previous studies, proposed that structures containing collagen within the muscle tendon unit (perimysium, endomysium) contribute to passive stiffness, mostly at the end range of movement, and that within the physiological range of muscle length change, passive stiffness can be attributed to structures within the myofibril (e.g.…”
Section: Discussionsupporting
confidence: 58%
“…However, this study did not evaluate changes in short-term diabetic patients. If we consider several reports that have shown that soft tissues exposed to a hyperglycaemic environment are stiffer [10], both our study and that of Salsich et al had unexpected findings. The latter [3], in an effort to find a solution to the contradiction between their study and reports of increased connective tissue stiffness in previous studies, proposed that structures containing collagen within the muscle tendon unit (perimysium, endomysium) contribute to passive stiffness, mostly at the end range of movement, and that within the physiological range of muscle length change, passive stiffness can be attributed to structures within the myofibril (e.g.…”
Section: Discussionsupporting
confidence: 58%
“…Further studies by the same investigators demonstrated that exogenous administration of D -lysine to streptozotocin-diabetic rats inhibited nonenzymatic glycation of Hb, serum albumin, and lens proteins [23]. Similar to D -lysine, L -lysine has also been reported to inhibit nonenzymatic glycation of plasma proteins [14]and nonenzymatic glycation-induced biomechanical properties of rat tail tendon fibers [20]. The observed prevention of a rise in glycosylated HbA 1 and glycation of GBM collagen by early institution of L -lysine is consistent with the above data.…”
Section: Discussionmentioning
confidence: 99%
“…These include acetylsalicylic acid [12, 13, 14, 15, 16, 17, 18, 19], L -lysine [14, 20], D -lysine [21, 22, 23], L -arginine [24], vitamin C [20, 25, 26, 27, 28, 29], vitamin E [30], bendazac [31], and aminoguanidine [4, 5, 6, 7, 8, 9, 10, 32, 33]. Other novel therapeutic agents have been shown to improve albuminuria and mesangial expansion in diabetic mice [34, 35]and rats [36], with type 2 diabetes melllitus.…”
Section: Introductionmentioning
confidence: 99%
“…Glycation can affect collagen in a number of ways: its ability to form precise supramolecular aggregates, the alterations in its charge profile, defects in the 143 144 G. K. REDDY formation of its fibrils, and hence its interaction with cells. In addition to the occurrence of biochemical and morphological manifestations, glycation has been shown to alter the biomechanical functioning of the connective tissues [15][16][17][18][19][20][21]. Both in vivo and in vitro studies have shown that reducing sugars, such as glucose and ribose, react with the amino groups of collagen and other proteins and form cross-linked AGEs in the tissue.…”
mentioning
confidence: 99%